Study on total lipit and free fatty acids extraction from heterotrophic marine microalga Schizochytrium mangrovei PQ6 - Minh Hien, Hoang Thi; Tam, Luu Thi; Thom, Le Thi; Ha, Nguyen Cam; Hanh, Luong Hong; Lan Anh, Hoang Thi; Hoai Thu, Ngo Thi; Hong, Dang Diem (Academia Journal of Biology, 2014)
This work aims to extract total lipid and free fatty acids from heterotrophic marine microalga Schizochytrium mangrovei PQ6 which was isolated from Phu Quoc island, Kien Giang province, Vietnam for producing bio-oil rich in omega-3 and omega-6 polyunsaturated fatty acids -PUFAs, especially docosahexaenoic acid (DHA; C22:6 omega-3), eicosapentaenoic acid (EPA; C20:5 omega-3) and docosapentaenoic acid (DPA; C22:5 omega-3/omega-6), this microalga was grown in 150 L fermentor to supply enough biomass for lipid extraction. The cell density, dry cell weight and total lipid were 125.51 ´ 106 cells/ml, 30.31 g/l and 56% of dry cell weight after 96 h of cultivation, respectively. Biomas of PQ6 strain have DHA concentration up to 32.98% of total fatty acids (TFA). Under the optimum conditions such as n-hexane; temperature at 70-75oC; continuous agitation for 4 hrs; for one time of extraction; biomass: solvent ratio as 1:10; temperature for drying biomass at 80oC; humidity of biomass at 0%, total lipid content has increased from 56% to 70% of dry biomass weight. The optimal hydrolyzation reaction condition for obtaining the free fatty acids have found out using chemical reaction with NaOH concentration of 1.8N dissolved in ethanol 70%; reaction temperature at 70oC for 3 hrs. The content of omega-3 and omega-6 PUFAs contains up to 60.937% of total fatty acids found in the free fatty acid, DHA and EPA contents take up 22.438% and 14.304%. Obtained free fatty acids in this study can be used as good quality material for producing the bio-oil rich omega-3 and omega-6 PUFAs such as DHA, EPA, DPA for functional food for human and feed for animals.